Dětské čtenářství v didaktických souvislostech a perspektivy neurovědních poznatků. / Didactic background of children's reading and perspectives of neuroscience. - Václav Jindráček; Jiří Škoda; Pavel Doulík (Czech Pedagogical Society, 2013)
The goal of this review is to look up research studies, that have by using the functional or electrophysiological methods investigated the activation of cortical parts of brain during reading or narrating astory (narrative or discourse), and by using reviews give the overview of the results which the selected works achieved. The first part of the report is devoted to the contemporary children reading in educational contexts in literary education. In the second part an overview of research studies mapping the activation of cortical parts of the brain during the process of reading and the understanding of narrative/discourse is provided. As a source of data, thefollowing databases were used (2007-2012): Medline, Bibliomedica, Science Direct, Web of Science, Google Scholar. 16 studies were included in the analysis. It has come to light, that the identified works considered the specifics of pubescent and prepubescent readers only in few isolated cases, yet in spite of that, gave extensiveoverview about the options that can be used to clarify the mechanisms of the process of reading a narrative text on the level of cortical activation of the brain. Sixteen research studies were included in the analysis. In the evaluated articles, great importance hasbeen given to the research of activity of brain parts/hemispheres in the process of construction of the so called situational models (during the segmentation of the narrative into individual parts/events) and defining contrasts that characterize neural correlates of inferential processes.